If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -5x = 8 + -4x Solving -4 + -5x = 8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -4 + -5x + 4x = 8 + -4x + 4x Combine like terms: -5x + 4x = -1x -4 + -1x = 8 + -4x + 4x Combine like terms: -4x + 4x = 0 -4 + -1x = 8 + 0 -4 + -1x = 8 Add '4' to each side of the equation. -4 + 4 + -1x = 8 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 8 + 4 -1x = 8 + 4 Combine like terms: 8 + 4 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| 81+5y=-4y | | 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) | | 213-4x=32x+21 | | 1/5(3x+12)=3(1-4x)+12 | | -x+4=5x+22 | | 2k+1=4 | | 6x+14=-51-7 | | c=0.10x+6 | | k(2.2)+k(1.8)+5=15 | | 12x=x/3 | | 6x+10=10x+2+5+1 | | 1/3(x+3)=1/6(2x+6) | | 6x+10=10x | | x+7/4=2x-7/4 | | 6x+7=3+8x-6 | | 22p-72=16-22p | | 11x-7x=-2 | | 3-6=2 | | x(3x)-5x=2 | | 5(y-3)=5-3y | | -(2x-1)=-5(2x+9) | | 1/8(x+8)=1/24(3x+24) | | 3x+5/4=4x-5/4 | | 3x-5(2x-1)=2(4x+7) | | g(2)=x^2-x | | 9x+27-6x+12=60 | | 6x+5=6x+21 |